A Comparative Study of Ishtar-Anahita Character in Iranian and Mesopotamian Myths with Aban Dokht in the Story of Samak-e Ayyar - Leila Mokhtariniya; Farzaneh Yousef Ghanbari; Ali Zahed (Matn/Pizhūhī-i Adabī, 2023)
One of the motifs in Iranian epic stories is the presence of mythological heroes and characters. Water goddesses and other goddesses are mythological figures that manifest in the form of well-known women in epics. Carefully examining the epic-heroic long story of Samak-e Ayyar, one can notice the function of such a belief in a female character in the story using a descriptive/comparative-analytical method and by citing the works of mythologists like Mehrdad Bahar and reflection on mythological hidden layers of Samak-e Ayyar's epic prose. Themes like love, beauty, underground imprisonment, being sentenced to death, freedom at the expense of losing the first beloved and finally rising to power for the female character of this epic story indicate that Abandokht in regard to her mythological arches can be a symbol of goddesses like Ishtar Mianroudi and Anahita. Based on this hypothesis, the authors have tried to conclude that the influence of Mianrouds and their liability to be influenced in Iranian myths led to the formation of common structures, one of which is the appearance of the similarities between the above-mentioned mythological goddess and Abandokht in the story of Samak-e Ayyar.